Time-Frequency Transforms for Classification of Power Quality Disturbances - Rodríguez, Alejandro; Aguado, Jose A.; López, Jose J.; Martín, Francisco; Muñoz, Francisco; Ruiz, Jose E. (IntechOpen, 2011)
None